Hubungan Antara Bimbingan Belajar Dirumah oleh Orangtua dengan Motivasi Belajar Siswa di SMA Negeri 4 Kota Jambi - Friska Vebina Sari; Rasimin Rasimin; Siti Amanah (Journal on Education, 2023)
The study is backed up by a large number of parents who are so busy with work that they do not provide learning support for their children, ata high school in the country of 4 cities, there is a high point in students' lack of learning motivation because their parents' average job is self-employed and fail to provide incentive for their children. The purpose of this study is to look at the relationship between the home guidance system and the student's motive for studying at sman 4 jambi city and the number of 81 students. Sampling withdrawal techniques using random sampling techniques. The result of research on parental guidance relationships with the motivation for student studies at sman 4 cities is categorized in a moderate correlation. Based on the results of angket processing Shared by researchers. It is known that the Pearson correlation value and product correlation analysis of the formula is 0.413.